Worth while WEALTH : An entrepreneur's guide to success that satisfies - Gomersall, Bob, Dr. (Great Britain, United Kingdom : Practical Inspiration Publishing, 2024)
"This is a handbook for a new kind of entrepreneur: the kind that wants to create not just a profitable business but a worthwhile life. With inspiration and insights from a wide range of business builders, Dr Bob Gomersall sets out a vision for a new kind of return on investment and shows you how to create this success for yourself, your way. Whether you re an established business leader or just feeling ready for a change, this is a blueprint for a better life and a better way of doing business." -- Publisher description
Includes index.
Keywords: Success in business; Entrepreneurship; Social responsibility of business